Teen Titans. Raven - Garcia, Kami (DC Comics, 2019)
Seventeen-year-old Raven Roth loses her memory and her foster mother in a tragic accident. She moves to New Orleans to heal and finish her senior year of high school. There she begins to grow close to new friends, her foster sister Max, and cute Tommy Torres but when strange things begin happening, Raven is forced to confront her past and the darkness inside her.